Amazing Faces - Hopkins, Lee Bennett; Soentpiet, Chris K. (New York : Lee & Low Books, 2010)
Presents illustrated poems focusing on universal emotions, as expressed by poets from diverse backgrounds, including Joseph Bruchac, Nikki Grimes, Lee Bennett Hopkins, Pat Mora, and Janet S. Wong.
Keywords: Emotions -- Poetry; American poetry -- Collections